Healthcare Business Intelligence: A Case Study of Universiti Utara Malaysia Health Center (PKU) - Ishola, Muraina Dada (2011)
Organizations, private or public, feel increasing pressures, forcing them to respond quickly to changing conditions and be innovative in the way they operate. Such activities require organizations to be agile and make frequent and strategic, tactical, and operational decisions. Making such decision may require considerable amounts of timely and relevant data, information, and knowledge. Every semester that UUM admits new students, they do subject them to medical screening which sometimes includes the staffs and returning students. However, the results of the medical test from the laboratory technologists and the doctors, such as patient diagnosis, treatment and medical prescription are currently kept in the PKU data repository for record purposes without being further explored for their managerial activities. Therefore, this research applied Business Intelligence (BI) method for exploring the PKU database repository. The data warehouse was built for the activities in PKU and a prototype was developed at the end, while the system is evaluated by the prospective users of the system at PKU. The result of this research (PKUBI) helps the PKU management by simplifying the technique needed for managerial decision making and forecasting future activities that would help the PKU. Also, the PKUBI is also useful to know the medical statistics of the patients in UUM and the drugs that need to be frequently ordered for.